PENERAPAN STRATEGI PEMASARAN POSITIONING, DIFFERENTIATION, BRANDING (PDB) DALAM MENENTUKAN KEUNGGULAN KOMPETITIF DESTINASI PARIWISATA - Fitri Ciptosari; Yohanes Paulus Hanny Wadhi (Universitas Nusa Cendana, 2023)
Marketing management is the most important job for tourism destination managers in increasing competitive advantage and maintaining market conditions (supply and demand). Marketing has an important role in increasing the number of tourist visits through the packaging of tourism products that have their uniqueness compared to similar tourism products owned by competitors. This study aims to build tourism destination branding through Positioning, Differentiation, and Branding marketing strategies. Through a case study method with a qualitative approach, this research explores the marketing management of tourist destinations through Positioning, Differentiation, and Branding (PDB) in building a competitive advantage for the Wae Bobok ecotourism destination. This study presents an analysis of the potential of tourist destinations and an analysis of the internal and external environment, which are then combined to determine the Positioning, Differentiation, and Branding of the Wae Bobok ecotourism destination. This study has limited perspectives from consumers or visitors. Therefore, further research is needed to measure the profile, behavior, expectations, and satisfaction of visitors to build a comprehensive destination marketing strategy. Keywords: Tourism Marketing; Marketing Management; Tourist Destination; Positioning; Differentiation; Branding